Pemantauan dan Pengaturan Proxy Server Dalam Pengaksesan Internet Dengan Otentikasi Berbasis Web - Santoso, Januar; Wijaya, Normandito; Siswandi, Khowi (ComTech: Computer, Mathematics and Engineering Applications, 2010)
The quick expanding user of World Wide Web (WWW) has been made a development in proxy server in limited access to the users. Therefore, it needs the limit with designing and implementing proxy server configuration system and authentication in internet web-based usage so it will ease in supervising and using internet facility. The method used is analysis and web-based system design. The expected result is the easier in supervising and controlling internet facility using proxy server and reducing the leaking of internet facility usage through authentication (security).